NASR HAMID ABU ZAYD DAN GAGASAN HERMENEUTIKA DALAM TAFSIR AL-QUR’AN - Imam Subchi (Mimbar Agama Budaya, 2020)
Abstract. This article reviews Nasr Hamid Abu Zayd's reinterpretation of sacred texts, according to which the Qur'an does contain general ethical guidelines but does not have answers to contemporary human problems. For him, humans can do many things from outside religion. With this model of thinking, it can help overcome obstacles and freezing in Islamic thought. Abu Zaid tried to do things based on traditional religious knowledge, to adapt the findings of modern linguistics and philosophical hermeneutic theory in analyzing the Qur'an and Islamic theology.Abstrak. Artikel ini mengulas reinterpretasi Nasr Hamid Abu Zayd terhadap teks-teks suci, yang menurutnya Al-Qur’an memang berisi pedoman etika umum namun tidak mempunyai jawaban atas problem-problem kemanusiaan kontemporer. Baginya, manusia mampu melakukan banyak hal dari luar agama. Dengan pemikiran model ini, dapat membantu mengatasi hambatan-hambatan dan kebekuan dalam pemikiran Islam. Abu Zaid berupaya melakukan hal-hal berdasarkan ilmu agama tradisional, guna mengadaptasi temuan-temuan lingusitik modern dan teori hermeneutika filosofis dalam menganalisis Al-Qur’an dan teologi Islam.